1979
DOI: 10.1002/art.1780221008
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage preservation and storage

Abstract: Articular cartilage slice explants were stored under various conditions, including freezing-thawing at various rates by using dimethyl sulfoxide (DMSO) as a cryoprotective agent, incubating in standard tissue culture medium (MEM Eagle:NCTC 13515% fetal calf serum) in 5% CO, and air at 4", 21", and 37"C, and incubating in standard tissue culture medium containing 200 pg/ml a-tocopherol (vitamin E) at 37°C after first ascertaining a dose-response curve of vitamin E. Results indicated that articular cartilage sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…An increase in shelf life will have a very significant impact on the treatment of cartilage lesions by expanding the availability of osteochondral allografts. While Brighton and co-workers showed promising findings using tissue culture techniques for cartilage maintenance nearly two decades ago, cold storage ($4 1C) is the current standard for osteochondral graft preservation and storage (Brighton et al, 1979). In the current study, we revisit the potential of using in vitro techniques for maintaining cartilage explants in long-term culture.…”
Section: Introductionmentioning
confidence: 98%
“…An increase in shelf life will have a very significant impact on the treatment of cartilage lesions by expanding the availability of osteochondral allografts. While Brighton and co-workers showed promising findings using tissue culture techniques for cartilage maintenance nearly two decades ago, cold storage ($4 1C) is the current standard for osteochondral graft preservation and storage (Brighton et al, 1979). In the current study, we revisit the potential of using in vitro techniques for maintaining cartilage explants in long-term culture.…”
Section: Introductionmentioning
confidence: 98%
“…Brighton et al [3] and Black et al [21 were the first to report extensive studies on the application of tissue culture techniques to cartilage preservation. They observed that cartilage slices stored in tissue culture medium at 37 ° C survived for as long as 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown variable results regarding the effect of storage on graft quality (Viidik and Lewin 1966;Brighton 1979;Woo et al 1986;Schachar et al 1994;Oates et al 1995;Smith et al 1996;Sammarco et al 1997;Williams et al 2003;Rohde et al 2004;Williams et al 2005;Malinin et al 2006;Pennock et al 2006;Lightfoot et al 2007;Williams et al 2007;Giannini et al 2008). Optimum refrigeration times for osteochondral allografts have been reported in the literature to be less than 5-7 days (Schachar et al 1994;Rohde et al 2004) or as long as 42 days (Williams et al 2007).…”
Section: Introductionmentioning
confidence: 89%